UNDERSTANDING THE CHALLENGES OF OUTCOME-BASED EDUCATION IN ENGLISH LANGUAGE TEACHING: A LITERATURE REVIEW - Susanti, Ika; Wiwik Mardiana; Krisdiana, AmyKrisdiana (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Outcome-Based Education (OBE) prioritizes measurable learning outcomes but often faces significant implementation challenges. This research explores the barriers to adopting OBE within English Language Teaching (ELT) by conducting a systematic literature review. Key challenges identified include issues with teaching methodologies, institutional support, curriculum design, and assessment practices. Teachers struggle to transition from traditional, teacher-centered approaches to student-focused methods, often due to inadequate training and resources. Additionally, aligning lessons with clear learning objectives and developing effective assessments remains difficult. Limited school support and resistance to change further complicate the adoption of OBE. This study provides valuable insights and offers recommendations for educators and policymakers, emphasizing the importance of targeted training, sufficient resources, and structured guidance to effectively implement OBE in English language education. Keywords: Outcome-Based Education, OBE, English Language Teaching